Suffering and sunset World War I in the art and life of Horace Pippin - Bernier, Celeste-Marie 1975- (Temple University Press, 2015)
For self-made artist and World War I soldier Horace Pippin - who served in the 369th African American infantry - war provided a formative experience that defined his life and work. His transformation of combat service into canvases and autobiographies whose emotive power, psychological depth, and haunting realism showed his view of the world revealed his prowess as a painter and writer. In Suffering and Sunset, Celeste-Marie Bernier painstakingly traces Pippin's life story of art as a life story of war. Illustrated with more than sixty photographs, including works in various media - many in full color - this is the first intellectual history and cultural biography of Pippin. Working from newly discovered archives and unpublished materials, Bernier provides an in-depth investigation into the artist's development of an alternative visual and textual lexicon and sheds light on his work in its aesthetic, social, historical, cultural, and political contexts. Suffering and Sunset illustrates Pippin's status as a groundbreaking African American painter who not only suffered from but also staged many artful resistances to racism in a white-dominated art world. -- from dust jacket
Includes bibliographical references (pages 465-480) and index
Keywords: Pippin, Horace -- 1888-1946 -- Criticism and interpretation; Pippin, Horace -- 1888-1946; Weltkrieg (1914-1918); World War, 1914-1918 -- Art and the war; African American painters -- Biography; Painters -- United States -- Biography; World War, 1914-1918 -- Personal narratives; Erster Weltkrieg; USA; Biografie